A tin mining acfivity by British Colonial and its impacf to environment in peninsular of Malaysia - Haliza Abdul, Rahman (Pusat Pengajian Sains Perubatan, 2010)
A tin mining industry is one of the oldest industry in Tanah Melayu since Sultanate of Malacca (Malay Dynasty). The historical of Dutch proved thai in year of 1649 there are 349 tons of tin bad been exported via the Malacca port. An evoke of tin industry has increasing the demand of tin used for the process of food canning and other types of industries and had prompted the British to sail all over the world and then colonized a rew·countries in Asian region to obtain the tin supply. However, the tin mining activity by the BritiSh cA>nialletl-a huge harmful impacts to the natural environment iri Peninsular Malaysia. Industrial rapid development by the British Colonial in end of 19"' centucy bad extremely changed the landscape at lhe most area of Peninsular Malaysia especially in the state of Selangor and Perak. There were many negative impacts had existed to environment caused by the tin mining activities such as piling of waste materials (tailing), soli erosion, river silting and sedimentation, degradation of water quality, flooding. land degradation, deforestation, wildlife species disruption, reduction of soil fertility as well. At the couple of decades after year 1910, notes that the impact to the nature cause by the tin mining activity left by British Colonial become more severe due to no effective control on waste disposal system during the mining activity.